HUMAN ENGINEERING AND ITS ROLE IN REDUCING JOB STRESS FOR EMPLOYEES OF YOUTH AND SPORTS FORUMS IN SALADIN GOVERNORATE - Dr. Thamer Turki Al-Mahlawi; Novan Salem Saleh Abdel (Proximus Journal Publishing, 2024)
The research aimed to Building a human engineering scale for employees of youth and sports forums in Salah al-Din Governorate. Building a measure of job stress for employees of youth and sports forums in Salah alDin Governorate. Identify the statistical differences between human engineering and job stress for employees of youth and sports forums in Salah al-Din Governorate. The research community was represented by employees of youth and sports forums in Salah al-Din Governorate, who numbered (208) employees who were chosen intentionally, while the application sample amounted to (135) employees. In order to achieve the research objectives, two scales of human engineering and job stress were built by following the steps and procedures for constructing standards and processing data. By using the Statistical Package for Social Sciences (SPSS). The researcher reached a set of conclusions, including the human engineering scale that was built by researcher Saleh to measure the human engineering of employees of youth and sports forums in Salah al-Din Governorate. The job stress scale was built by researcher Saleh to measure the job stress for employees of youth and sports forums in Salah al-Din Governorate
Keywords: Ergonomics; job stress; youth and sports forum